Laparoscopic bowel resection in the presence of a lumbo-peritoneal shunt: a rare case. Issue 9 (16th September 2020) - Neagle, Gregg; Bhatti, Emma; Hawkins, Martyn; Rodger, Chris
Abstract : The presence of a cerebrospinal fluid (CSF) shunt was previously considered a contra-indication to laparoscopic surgery, however, case reports appeared that describe laparoscopic surgery proceeding with no adverse outcomes in such patients. The majority of these reports relate to laparoscopic cholecystectomy. Here we present what we believe to be only the second report of a patient undergoing laparoscopic bowel resection in the presence of a lumbo-peritoneal shunt. With this case we aim to add to the evidence that more major laparoscopic procedures can be performed safely in the presence of CSF shunts and with a brief review of the current evidence, have suggested appropriate monitoring and precautionary measures for approaching these procedures.